Dirt femme [compact disc] - Tove Lo, 1987- (Pretty Swede Records, 2022)
Grammy Award-nominated artist Tove Lo releases her fifth studio album. The album tracklist boasts an impressive lineup of special guests, including SG Lewis, Channel Tres, and First Aid Kit.